Sugarcane filter cake waste as natural antibacterial agent against Xanthomonas citri subsp citri - Guerra, Laureana (2023)
The sugarcane filter cake waste (SFCW) is the main solid waste product generated during sugar production, without final disposition; and this work suggests that it could be reutilized to control Xanthomonas citri subsp citri (X. citri), the etiologic agent of citrus canker, in lemons. The aim of this work was the identification of phenolic compounds present in SFCW, and the evaluation of its antibacterial activity against X. citri, in vitro and in vivo using preventive and curative methods in lemons. Also, the antibacterial mode of action of SFCW on X. citri and its effect on Xanthan production were carried out. Results demonstrated the presence of phenolic compounds in SFCW and that quercetin, rutin, catechin and caffeic acids were the majority phenolic compounds. Phenolic extract had bactericidal action at high concentrations, inhibit the biofilm formation and reduce the exopolysaccharide production. The Inhibitory concentrations (IC50, IC90) and the Letal concentrations, LC50 and LC90 were determined. All individual phenolic compounds reduced the growth of X. citri and the effect increased with the concentration. In lemons, preventive and curative methods were effective to reduce X. citri survey. Moreover, our investigations showed that phenolic fraction of SFCW were effective to produce cellular death of X. citri in lemon. Our results demonstrated that SFCW could be reused as natural antibacterial agent against X. citri, etiologic agent of citrus canker in lemons.